Vibration Response of Composite Slab under Human-induced Dynamic Load: A Review - Roslan, Aina Syafawati; A. Majid, Masni; Mohd Jaini, Zainorizuan; Sutiman, Nur Adidah (Recent Trends in Civil Engineering and Built Environment, 2020)
In the construction industry, especially that related to the application of industrialized building system (IBS), floor system from the composite slab is highly demanded to provide optimum design, cost-saving, and constructional efficiency were lead in offering on an economical solution. One of the most critical elements that should be focused on while designing the composite flooring system is serviceability evaluation due to vibration where will affect human comfort. The design criteria proposed in evaluating the comfort criteria, namely as (i) acceleration limit (ii) natural frequency limit and (iii) deflection limit. This paper summarized numerous vibration response studies of the composite slab with different material composition types such profiled steel sheet dry board (PSSDB), profile steel sheet with concrete infill (PSSC), and profiled steel sheet dry board with concrete infill (PSSDBC). The effect of various parameters on a composite slab vibration response was studied and discussed in detail by classification. Finally, on the summary table of the previous study was noted, presenting the parameter studied and the remarks on each study conducted.